Optimization of Project-Based Learning with Inquiry Approach in Rotational Dynamics Study - Syahril; Desmelinda, Ersa (Jurnal Pendidikan Fisika, 2026)
Rotational dynamics is frequently taught as an abstract, equation-centered topic, which can reduce engagement and hinder the growth of inquiry and process skills. This study aimed to optimize project-based learning (PjBL) through an open-inquiry approach to improve students’ learning outcomes, classroom activity, and science process skills in rotational dynamics. A quasi-experimental nonequivalent control-group design was conducted at MAN 2 Kepulauan Meranti with 55 eleventh-grade students (experimental n=26; control n=29). The experimental class learned through PjBL integrated with open inquiry by designing and building a mini gear-based machine prototype from recycled cardboard as an investigative medium, while the control class received conventional instruction. Data were gathered using pretest–posttest cognitive tests, classroom activity observations, science process skills rubrics, and student response questionnaires. The experimental class demonstrated higher overall activity (75%) than the control class (57%). Student responses indicated the intervention was enjoyable (77%) and helped understanding (69%). Science process skills in the experimental class were rated good, with strong performance in using tools/materials and communicating results (mean score 4.0 each), and adequate performance in project design (3.2), conducting experiments (3.0), interpreting data (3.0), and reporting. Cognitive achievement also improved: the experimental class reached a higher posttest mean (79.6) than the control class (73.9) and a higher normalized gain (N-gain=0.74 vs 0.67). The novelty of this study lies in a low-cost, scalable PjBL–open inquiry sequence that leverages recycled materials to produce tangible prototypes that make rotational concepts observable and testable. In conclusion, optimizing PjBL with open inquiry can enhance engagement, process skills, and conceptual mastery, offering a practical contribution to physics education for more meaningful and skills-oriented instruction.